Asymptomatic Coronavirus infections (Eurasian Journal of Research, Development and Innovation, 2024)
According to the World Health Organization (WHO), the emergence of viral diseases represents a serious public health risk, and as the pandemic of the novel coronavirus has been developed, an increasing number of asymptomatic patients have been found, causing worldwide anxiety. This study aimed to detect the role of asymptomatic people in transmission and spread of disease. The reviewed studies around the world showed considerable variations in proportion of asymptomatic COVID-19 cases among different groups (children, pregnant women, elderly, others). Most of the studies confirmed the important role of these cases in COVID19 transmission and as a result, the importance of quantification of asymptomatic infections as it is fundamental for effective public health responses to prevent and control the outbreaks